Primary Mediastinal B-Cell Lymphoma: Novel Precision Therapies and Future Directions - Chen, Huan; Pan, Tao; He, Yizi; Zeng, Ruolan; Li, Yajun; Yi, Liming; Zang, Hui; Chen, Siwei; Duan, Qintong; Xiao, Ling; Zhou, Hui (Frontiers in Oncology, 2021)
Primary mediastinal large B-cell lymphoma (PMBCL) is a distinct clinicopathologic disease from other types of diffuse large B-cell lymphoma (DLBCL) with unique prognostic features and limited availability of clinical data. The current standard treatment for newly diagnosed PMBCL has long been dependent on a dose-intensive, dose-adjusted multi-agent chemotherapy regimen of rituximab plus etoposide, prednisone, vincristine, cyclophosphamide, and doxorubicin (DA-R-EPOCH). Recent randomized trials have provided evidence that R-CHOP followed by consolidation radiotherapy (RT) is a valuable alternative option to first-line treatment. For recurrent/refractory PMBCL (rrPMBCL), new drugs such as pembrolizumab and CAR-T cell therapy have proven to be effective in a few studies. Positron emission tomography-computed tomography (PET-CT) is the preferred imaging modality of choice for the initial phase of lymphoma treatment and to assess response to treatment. In the future, baseline quantitative PET-CT can be used to predict prognosis in PMBCL. This review focuses on the pathology of PMBCL, underlying molecular basis, treatment options, radiotherapy, targeted therapies, and the potential role of PET-CT to guide treatment choices in this disease.